Analysis of the construction of collective identities in textbooks: treatment of the War of Independence in the last decades - Ortega Cervigón, José Ignacio; Rodríguez Garrido, Juan Esteban (Historia y Memoria de la Educación, 2017)
History manuals influence the individual imaginary of the pupil, as well as the creation of a collective memory and a number of cultural stereotypes. Similarly, they can contribute to the stigmatization of an epoch or of an historical figure, or to their lionization, for all eternity, of the figure of a certain king or social group. The textbook is the most widely used didactic resource for approaching the subject of History. The different perspectives of its analysis have propitiated an interesting line of investigation in Didactics of the History. This is the reason for our interest in scrutinizing the way in which these books have presented to our students the history, facts and prominent figures of the War of the Independence, one of the historical processes most resorted to in the creation and consolidation of collective identities in Spain. To obtain a significant sample in our study, we use examples of the most representative publishing houses as well as texts studied in Secondary Education and published at different times in the last four decades.